Building Synergy Strategy “Cawas Lurik Centre” Association to Preserve the Existence of Crafting Business - Widiastuti, Theresia; Rizali, Nanang; Anantanyu, Sapja; Waluyo, Sugeng Edi (International Journal of Emerging Trends in Social Sciences, 2017)
Javanese is one of Indonesia’s ethnic living in the region of Central Java, Yogyakarta and East Java. Having three typical types of traditional are clothing, namely batik, lurik (striated weaving), and jumputan (tye dye). In Klaten district, Central Java found striated weaving centers, one in the Cawas district. The main problem faced by the artisans of striated weaving in this place is likely difficult in marketing products, because they have to compete the other types of textile markets. As a result, the craftsman run out of capital, and led to ups and downs state. Therefore, they work together in a association called the Society of Craftsmen Cawas Lurik Center. This study aims to determine how the artisans of striated weaving Cawas seek to be able to continue their efforts. This research paper uses a form of qualitative research using case study strategy with phenomenological approach. The results showed (1) the artisans joined the association as a forum for cooperation between them; (2) creates synergy among craftsmen to improve the ability and knowledge, and (3) develop synergies with the outside association to strengthen the group in order to have a bargaining position in the middle of the competition.